BASLAWÍSH KLASS OQÍWSHÍLARÍNÍŃ KITAP PENEN ISLESIWINDE MUǴALLIM HÁM ATA-ANANÍŃ ǴAMQORLÍǴÍ - Abdijabbarova, J. (SCIENCE and SOCIETY, 2017)
The article deals with the mutual activity of teachers, parents and school children in the work with a book. The author of the article presents methods and gives recommendations how to develop the learner’s interest to readind books. The author also states about the importance of keeping the daily schedule.
Keywords: a teacher; parents; daily schedule; work with books; to teach self education; computer; internet; site; school library